For the common good : essays of Harold Lewis - Lewis, Harold (Brunner-Routledge, 2003)
Social work literature often reflects powerful ahistorical tendencies. In recent years, these tendencies have produced analyses of social issues that lack awareness of both the contemporary environment and the historical forces that shaped it.